Stories of the Old World - Church, Alfred John. (Auckland : The Floating Press, 2014)
The Roman poet Virgil is regarded as one of the most significant literary figures of the ancient world. His major contribution was the epic poem of battle the Aeneid. In Stories of the Old World, author Alfred Church John presents many of Virgil's most beloved tales, as well as some from other ancient scribes, in an easy-to-read translation that will engage a wide range of readers.
Title; Contents; Note; The Story of the Argo; Chapter I; Chapter II; Chapter III; The Story of Thebes; Chapter I; Chapter II; The Story of Troy; Chapter I; Chapter II; Chapter III; Chapter IV; Chapter V; Chapter VI; Chapter VII; Chapter VIII; Chapter IX; Chapter X; Chapter XI; Chapter XII; Chapter XIII; Chapter XIV; The Adventures of Æneas; Chapter I; Chapter II; Chapter III; Chapter IV; Chapter V; Chapter VI; Endnotes
Description based upon print version of record.
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Roman -- Juvenile literature; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Antiquities & Archaeology; Electronic books